2014
DOI: 10.1007/s12306-014-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Repair of distal biceps tendon acute ruptures with two suture anchors and anterior mini-open single incision technique: clinical follow-up and isokinetic evaluation

Abstract: Our study shows that mini-open access and fixation with two suture anchors achieved in medium-term excellent functional and cosmetic results needed short rehabilitation times and is minimally invasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Our present study shows that clinical outcomes are comparable to those reported previously in the literature 1,7,9,17,19,24 (see Table 2). All patients regained full elbow range of motion at an average of 5.4 months and demonstrated satisfactory functionality with an average QuickDASH score of 6.5.…”
Section: Discussionsupporting
confidence: 91%
“…Our present study shows that clinical outcomes are comparable to those reported previously in the literature 1,7,9,17,19,24 (see Table 2). All patients regained full elbow range of motion at an average of 5.4 months and demonstrated satisfactory functionality with an average QuickDASH score of 6.5.…”
Section: Discussionsupporting
confidence: 91%
“…Early diagnosis and repair are preferred. 31,38,39 All studies demonstrated good to excellent results when evaluating the DASH score, the Mayo Elbow Performance Score (MEPS) and Morrey Elbow Score (MES) further justifying the utility of surgical fixation. Since Morrey et al's 51 original report on outcomes of distal biceps repairs in which 97% of flexion strength and 95% of supination strength were restored, many other studies have been reported in the literature.…”
Section: Results Of Operative Treatmentmentioning
confidence: 98%
“…The checklist consists of 27 questions, with a total possible score of 28 for randomized studies and 25 for nonrandomized studies. Downs and Black score ranges were given corresponding quality levels according to previous literature: excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19), and poor (14). Only randomized studies could achieve a quality level of excellent according to the scoring method of the Downs and Black checklist.…”
Section: Assessment Of Risk Of Bias and Quality Of Evidencementioning
confidence: 99%